ANALISIS LUKA EMOSIONAL DAN RESILIENSI PSIKOLOGIS DALAM NOVEL BROKEN STRINGS: PERSPEKTIF TANPA ROMANTISASI DAN IMPLIKASINYA BAGI BIMBINGAN DAN KONSELING - Putri Ayu, Siska; Akhmad Harum; Aswar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze emotional wounds and psychological resilience in the novel Broken Strings by Aurellie from a non-romanticization perspective, as well as to examine its implications for guidance and counseling. The study employed a qualitative approach using qualitative content analysis. The data consisted of textual excerpts from the novel representing emotional wounds, toxic relationships, psychological impacts, and resilience processes. Data were collected through document study with in-depth reading, while data analysis was conducted through thematic categorization and interpretation based on psychological and guidance and counseling perspectives. The findings reveal that emotional wounds in the novel stem from insecure family relationships and toxic interpersonal relationships, which lead to feelings of helplessness, fear, and emotional numbness. However, the main character demonstrates a process of resilience through self-awareness, assertiveness, social support, and the ability to reframe experiences adaptively. This study emphasizes the importance of a non-romanticization perspective in understanding emotional wounds and highlights its implications for guidance and counseling in strengthening emotional literacy, promoting healthy relationships, and developing psychological resilience.